2016
DOI: 10.4038/jccpsl.v21i1.8065
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of asthma among selected garment factory workers at the Free Trade Zone, Ekala

Abstract: ObjectiveTo determine prevalence of bronchial asthma (BA) and its correlates and respiratory functions among selected garment factory workers (GFW) at the Free Trade Zone, Ekala. MethodsThis consisted of a cross sectional descriptive and an analytical study. It was conducted at three selected garment factories and a clinic setting in Ekala. Study group for first component included 674 GFW who have worked for 1 or more years at the current garment factories. Control group for second component included 100 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…Increased age group, designation as a jobber, helpers, machine operators, being illiterate, having BMI of <18.5 and higher dust exposure were the factors found to be associated with one or more respiratory symptoms and illnesses. We found a higher prevalence of asthma (17%) compared to another study among textile workers (5%) 20 , and the general population of Karachi (11%) 21 , but lower than among Sri Lankan garment workers (32% for symptoms-based asthma) 22 . Other than a different definition used in the Sri Lankan study, these differences could also be due to some specific workplace factors like use of different dyes & chemicals at the selected millstherefore, results need to be interpretated with caution.…”
Section: Discussioncontrasting
confidence: 67%
“…Increased age group, designation as a jobber, helpers, machine operators, being illiterate, having BMI of <18.5 and higher dust exposure were the factors found to be associated with one or more respiratory symptoms and illnesses. We found a higher prevalence of asthma (17%) compared to another study among textile workers (5%) 20 , and the general population of Karachi (11%) 21 , but lower than among Sri Lankan garment workers (32% for symptoms-based asthma) 22 . Other than a different definition used in the Sri Lankan study, these differences could also be due to some specific workplace factors like use of different dyes & chemicals at the selected millstherefore, results need to be interpretated with caution.…”
Section: Discussioncontrasting
confidence: 67%
“…The OR of asthma was found to increase by about 1.6–1.9 when exposed to tobacco smoke in Pakistan 39. Studies in selected groups in Sri Lanka also found that certain occupations, such as working in a garment factory, increased the OR of asthma to 3.5 45. These associations are also evident in a systematic review that looked into the risk factors of asthma in Asian population 46.…”
Section: Discussionmentioning
confidence: 84%
“… 39 Studies in selected groups in Sri Lanka also found that certain occupations, such as working in a garment factory, increased the OR of asthma to 3.5. 45 These associations are also evident in a systematic review that looked into the risk factors of asthma in Asian population. 46 Furthermore, studies in developed countries like the USA, Spain and Finland also showed that the adult onset of asthma was significantly associated with parental asthma (OR 4.5), smoking habit (OR 2.0), male gender (OR 2.0) and chronic comorbidities (OR 2.7).…”
Section: Discussionmentioning
confidence: 86%